CRAFTING AN ENGLISH WORKBOOK BASED ON STUDENTS' NEEDS AND MULTIPLE INTELLIGENCES - Ishak, Samsudin R.; Talib, Rasuna R; Bouti, Suleman (Indonesian EFL Journal, 2023)
Diversity is celebrated in the newly promoted Emancipated Curriculum. However, providing English materials that suit to students’ diversity was quite challenging for English teacher at grade VII in rural area since the students never experience learning English at elementary school. This study is the second part of need assessment of the research and development of a Multiple Intelligences-based English Workbook. The study aims to explore the need analysis covering target needs and learning needs of 27 seventh grade students at SMP Negeri 4 Randangan Satu Atap, Pohuwato, Gorontalo, Indonesia in learning English at the first year by using need assessment questionnaire. From the online administration, it is found that on the target needs, students preferred learning English to communicate and perceived that writing, speaking, and pronunciation are the most required skills to have. In terms of learning needs students preferred online and updated content on YouTube, TikTok, Instagram and other digital sources; to be discussed in a small-group settings which enable ones to express ideas and reduce teacher’s talk. The findings indicate the importance of the inclusion of authentic materials, representation of gender, occupation, and religion including the accessibility of the embedded link to the original sources. Those of which are in line with the promoted diagnostic assessment in Emancipated Curriculum.Keywords: Diversity; emancipated curriculum; need analysis; target needs; learning needs; multiple intelligences, workbook.